Ámbito de hogar, preferencia de hábitat y patrones de actividad del zorro de Sechura Lycalopex sechurae (Mammalia: Canidae) en el Desierto de Sechura, noroeste del Perú - Carrasco-Escudero, Luiggi (2024)
The Sechura fox (Lycalopex sechurae) is a little-studied species despite being common in northwestern Peru and listed as Near Threatened internationally. This study presents the home range, habitat preference, and activity patterns of L. sechurae in two locations of the Sechura Desert: The Mangroves of San Pedro de Vice (MSPV) and the Illescas National Reserve (RNI). Using GPS collars, the minimum convex polygon method, and the Kernel estimator (KE), the home range of four female individuals (two from each site) was calculated. Additionally, the GPS location data were used to estimate activity patterns and habitat preferences for each individual. The home range of females from MSPV was 0.6 and 1 km² (95% KE), whereas, for the RNI, it was 3.5 and 25.1 km² (95% KE). Females from MSPV preferred dry forest (54.8% and 76.1%), while those from RNI favored desert scrub (64.3% and 64.5%). All individuals exhibited cathemeral behavior, with increased nocturnal activity. Our results demonstrate variability in home range sizes, similarity in activity patterns compared to other studies, and highlight the importance of dry forest and desert scrub as resource-rich habitats for Lycalopex sechurae.